EFFECTIVENESS OF THE ICARE MODEL INTEGRATED WITH DESMOS: IMPROVING MATHEMATICAL CONCEPTUAL UNDERSTANDING - Nova Riani; Winanda Marito; Lulu Melati Iskandar; Muhammad Azri Juliandry; Lambenturna Berutu (JURNAL EDUSCIENCE, 2026)
Purpose – This research compared students’ understanding of mathematical concepts when taught through two different approaches: conventional instruction and the ICARE model (Introduction, Connect, Apply, Reflect, Extend) supported by the Desmos application in the topic of quadratic equations. Despite growing evidence on the individual benefits of the ICARE learning model and the Desmos application, limited empirical research has examined their systematic integration within each ICARE phase to improve secondary students’ conceptual understanding of quadratic equations.Methodology – The study adopted a quasi-experimental design with a posttest-only control group. A total of 45 ninth-grade students from SMP Manunggal Medan participated in the 2025/2026 academic year, comprising 23 in the control class and 22 in the experimental class. The instrument was a conceptual understanding test consisting of open-ended questions, validated by experts. Data were analyzed using an independent sample t-test.Findings – The results showed a significant difference between the two groups (p < 0.001). The experimental class obtained an average score of 76.09, while the control class reached only 59.65. Distribution analysis also revealed that 86.4% of students in the experimental group were categorized as good to very good. In comparison, 78.2% of students in the control group were categorized as poor to very poor. These outcomes suggest that the ICARE model, combined with Desmos, is efficacious in improving students' conceptual understanding of mathematics and in narrowing individual achievement gaps.Contribution –In practice, the findings underscore the importance of preparing teachers to integrate technology into their teaching practices, thereby making learning more interactive, collaborative, and student centered.